2000
DOI: 10.3758/bf03200268
|View full text |Cite
|
Sign up to set email alerts
|

Event-duration discrimination by pigeons: The choose-short effect may result from retention-test novelty

Abstract: Pigeons trained on a conditional event-duration discrimination typically "choose short" when retention intervals are inserted between samples and comparisons.In two experiments, we tested the hypothesis that this effect results from ambiguity produced by the similarity of the novel retention intervals and the familiar intertrial interval by training pigeons with retention intervals from the outset and, for one group, in addition, making retention intervals distinctive from the intertrial intervals. In Experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 18 publications
2
18
0
Order By: Relevance
“…Similarly, t Dorrance, Kaiser, and Zentall (2000) have shown that when pigeons are familiar with the delays used in testt ing, matching accuracy is better than when they are not (Sherburne, Zentall, & Kaiser, 1998; see also Spetch & Rusak, 1989). These results suggest that the typical retenf tion function may consist of two components: a loss of matching accuracy resulting from the delay (or a loss in sample discriminability) and a generalization decrement d related to the difference in delay between training and g ( , ) testing (see White, 2001 …”
mentioning
confidence: 78%
See 1 more Smart Citation
“…Similarly, t Dorrance, Kaiser, and Zentall (2000) have shown that when pigeons are familiar with the delays used in testt ing, matching accuracy is better than when they are not (Sherburne, Zentall, & Kaiser, 1998; see also Spetch & Rusak, 1989). These results suggest that the typical retenf tion function may consist of two components: a loss of matching accuracy resulting from the delay (or a loss in sample discriminability) and a generalization decrement d related to the difference in delay between training and g ( , ) testing (see White, 2001 …”
mentioning
confidence: 78%
“…The pigeons averaged 85.3% correct matching responses at the 0-sec delay and declined to 64.5% correct at the 4-sec delay, a difference of 20.8%. However, when Dorrance et al (2000) trained pigeons with 0-, 1-, 2-, and 4-sec delays using a similar sample discrimination and, after they had attained a criterion of 75% correct at the 0-sec delay, tested them for 15 sessions, they found that the pigeons averaged 87.9% correct matching the experimental group had only 25% as many 0-sec delay trials per session as did the pigeons in the control group, the difference in sessions to criterion for 0-sec delayed matching between the experimental and control groups did not reach statistical significance [two-tailed t(6) 1].…”
Section: Discussionmentioning
confidence: 99%
“…One is instructional ambiguity/confusion between the dark s-c delay and the dark ITI (Dorrance et al, 2000;Sherburne et al, 1998;Zentall, 1997Zentall, , 1999Zentall, , 2007. If pigeons confused a dark s-c k delay with a dark ITI, they may have expected s d to be presented following an extended dark s-c k delay instead of c. On these trials, pigeons may have responded on the basis of the comparison of a fresh memory of c f to no memory of s. In other words, although they can clearly differentiate s from c, they may have responded as if no s had been presented on that trial.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies using SDMTS have demonstrated that if the ambient illumination conditions during the ITI are dif-f f ferent from those during the DI, then the choose-short ef-f f fect does not occur, and a symmetrical decline in accuracy as a function of DI length is observed for short-and longsample durations (Dorrance et al, 2000;Sherburne et al, 1998;Spetch & Rusak, 1992). However, as was illustrated by Kelly and Spetch (2000), simply differentiating the ITI from the DI in the SDMTS procedure may not necessarily eliminate the choose-short effect.…”
Section: Methodsmentioning
confidence: 99%
“…However, when the delay interval was illuminated by the houselight, there was a slight choose-few effect for Group Dark, and no response bias effect for Group Light. The response bias patterns observed appeared to have been due to instructional ambiguity (Dorrance, Kaiser, & Zentall, 2000;Sherburne et al, 1998;Zentall, 1997Zentall, , 1999Zentall, , 2005. Although the term instructional ambiguity has most often been used to refer to similarity between the delay interval and the ITI, in this case the ambiguity comes from the similarity of the delay interval to the gap between light flashes.…”
mentioning
confidence: 92%